Covering the Deceased’s Heads with Pottery Vessels: Insight from Late and Ptolemaic Period Necropolis in Saqqara West - Radomska, Małgorzata (Études et Travaux, 2025)
Among the more than 700 burials of the Late and Ptolemaic periods discovered by the Polish-Egyptian Archaeological Mission in Saqqara West, in the case of two burials the heads of the deceased were covered, respectively, with a vessel and half a vessel. The paper addresses the unique nature of this practice in view of the Saqqara necropolis in the last centuries BC, when cartonnage masks used for covering deceased heads begin to dominate in the Egyptian funerary tradition. By analysing the archaeological context, textual and material evidence on head protection in Egypt from the Old Kingdom to the Ptolemaic period, the author attempts to determine the origin, the significance and reason for exceptional treatment of these two deceased.